AICAR Administration Attenuates Hemorrhagic Hyperglycemia and Lowers Oxygen Debt in Anesthetized Male Rabbits - Huang, Yi; Ratz, Paul H.; Miner, Amy S.; Locke, Victoria A.; Chen, Grace; Chen, Yang; Barbee, Robert W. (Frontiers in Physiology, 2017)
Background – Many strategies have been utilized to treat traumatic shock via improved oxygen delivery (DO2), while fewer have been used to in an attempt to reduce oxygen demand (VO2). The cellular energy sensor 5’ adenosine monophosphate-activated protein kinase (AMPK) has the potential to modulate both whole-body DO2 and VO2. Therefore, we determined the effect of the AMPK activator AICAR (5-aminoimidazole-4-carboxamide 1-β-D-ribonucleoside) given acutely or chronically on key metabolites, hemodynamics and oxygen consumption/delivery before and during hemorrhage in anesthetized male rabbits. Methods – Chronically treated animals received AICAR (40 mg/kg/day, IV) for 10 days prior to hemorrhage, while rabbits in the acute study were infused with AICAR (7.5 mg/kg bolus, 2 mg/kg/min infusion) or vehicle (0.3 ml/kg saline bolus, 0.03 ml/kg/min infusion) IV for 2 hours prior to severe hemorrhage. Both acutely and chronically treated animals were sedated (ketamine/xylazine cocktail) the morning of the terminal experiment and surgically prepared for hemorrhage, including the implantation of arterial and venous catheters (for blood removal/sampling and drug/vehicle administration) and thoracotomy for implantation of transit-time flow transducers (for cardiac output determination). Results - AICAR given acutely lowered arterial blood glucose and increased blood lactate levels before hemorrhage, and abolished the well-documented hemorrhage-induced hyperglycemia seen in vehicle treated animals. Animals given AICAR chronically had blunted hemorrhage-induced hyperglycemia without prior baseline changes. Chronically treated AICAR animals showed significantly lower lactate levels during hemorrhage. Rabbits receiving AICAR both acutely and chronically experienced similar falls in mean arterial pressure, cardiac output and hence DO2 to their vehicle counterparts throughout the hemorrhage period. However, rabbits treated either acutely or chronically with AICAR accumulated lower oxygen deficits and debt during hemorrhage compared to vehicle-infused controls. Conclusions - The oxygen debt data suggest that AMPK activation could decrease trauma associated morbidity and mortality, perhaps by mechanisms related to increased glucose utilization. Additional studies are needed to investigate the effects of AICAR and associated mechanisms of action when given during resuscitation from hemorrhage.